From liberal to predatory mass media in post-communist Lithuania - Matonytė, Irmina (Žurnalistikos tyrimai, 2009)
Referring to the concepts, communicative democracy is defined as free, open and democratic communication organized around three equally legitimate public sphere actors – politicians, journalists and public opinion, and populism is understood as good, entertaining and effective communication with people, eroding basic functions of the political parties (institutionalization of ideological conflicts) and politicians (representation), the paper provides insights about the dangers to quality of democracy if the free mass media gets utterly away from political parallelism. Special attention is placed on the tendencies of media personnel to be active in the political life. The paper conceptualizes a tremendous decrease (by one third) in public trust in mass media in Lithuania, observed from 1998 to 2009 and interprets this change as a cumulative result of the post-communist illstructured political field under pressing liberalization and democratization coupled with specific patterns of the Lithuanian political culture and public sphere. In the conditions of a still relatively high public trust in mass-media and scarce foreign ownership of the mass-media outlets in Lithuania, the local media barons are able to produce and impose their own public-agenda. The Lithuanian massmedia and government relations evolve along the lines of the zero-sum game: they seek to control each other, and at the same time try to avoid being controlled by the other, while any other pattern of inter-relations does not appear as viable and appropriate. INTUNE project survey (2009) shows that the media elite’s influence in the national decision making process is significantly higher in Lithuania than, for instance, in Germany or Hungary.Key words: populism, communicative democracy, mass-media ownership, public sphere, public trust.